THE PRE-SERVICE TEACHERS’ REFLECTION IN ENGLISH FOR YOUNG LEARNERS TEACHING PRACTICE - Kharisma Naidi Warnanda Sabgini; Khoiriyah Khoiriyah (English Review: Journal of English Education, 2020)
This study aimed to explore the use of self-reflection for the pre-service teachers (PSTs) in an English for Young Learners teaching practicum. Through conducting classroom observation, semi-structured interview, and document analysis, the result of this study revealed that PSTs are able to develop their teaching knowledge and teaching skills in term of classroom management, language pedagogy, and preparation trough having self-reflection. Further, the usage of video recording provides self-critical and continuity for the pre-service teacher. Teaching reflection is projected to improve the teaching practice. Doing reflection in teaching practice is immensely important for professional development as student teachers are prepared to be a professional educator.  As a result, the implication of this study will be further discussed.